Comparison of Manifestations in Pulmonary Tuberculosis Patients with Conventional and Electric Cigarettes Smoking Habits - Rahma Ayu Larasati; Roosteriana Tris Tanicka; Ryamirza Pandu Wicaksono (Faculty of Medicine and Health Universitas Muhammadiyah Jakarta, 2025)
Background: Despite being a preventable and curable disease, Tuberculosis (TB) is still a major global health threat and the second leading cause of death due to an infectious agent worldwide. Cigarette smoke (CS) exposure is a key risk factor for both active and latent TB. Recently, E-cigarettes became widely known as a healthy alternative to conventional smoking, although their impact on TB is not yet well understood. Purposes: The objective of this study is to compare the clinical characteristics of pulmonary tuberculosis patients among users of e-cigarettes and conventional cigarettes. Methods: This is a descriptive observational analytic study with a sectional design and a purposive sampling technique to obtain 52 samples. The clinical manifestations were assessed by interview and secondary data. The data were analyzed using the Mann-Whitney U-test in SPSS. Laboratory findings and other data were investigated from medical records. Result: This study found that 60.7% are conventional smokers and 39.3% are e-cigarette smokers. This study also found no significant differences in terms of treatment duration (p = 0.752), drug sensitivity test (p = 0.826), and leukocyte level (p = 0.402). Conclusion: This study deduced that tuberculotic smoker patients who smoke conventional or e-cigarettes develop the same clinical manifestation.